Leachate toxicity assessment and bioremediation of leachate contaminated soil / Emenike Chijioke Uche - Uche, Emenike Chijioke (2013)
Chemical evaluations and characterization had often served as the commonly adopted options for assessing the potential impact of pollutants, which at the same time provide insight into the possible remediation technologies. However, heterogeneous substances may not be best studied in aforementioned forms because of the varied characteristics and concentrations of the discrete components. Leachate which is the liquid by-product of waste decomposition in landfills or dump sites is one such heterogeneous fluid that can easily pollute the environment (terrestrial and aquatic). With increase in waste generation in Malaysia, leachate production becomes inevitable especially as landfilling is the ultimate predominant waste disposal option. An average of 300,000 L of leachate is produced daily from each landfill and there are over 200 landfills in operation. Considering the high distribution of waste disposal sites in Malaysia, the study was designed to characterize leachate from the different landfill types in relation to their operational status. It aimed to assess the mortality effects of the leachate on aquatic life such that leachate toxicity index can be proposed. Similarly, the study was undertaken to investigate a possible accumulation of heavy metals in fish species due to leachate pollution and at the same time adopting a bioremediation option that will help remove the heavy metal that percolate in the soil due to leachate leaks, as a way of preventing heavy metals from getting to nearby surface water. Various methods adopted in the study ranged from the physico-chemical characterization of leachate, acute toxicity exposure, histopathology, to microbial characterization and bioaugmentation of leachate contaminated soil. Microsoft Excel, SPSS, EPA Finney’s Probit and Datafit were statistical tools used in the study. Some similarities were found among the characterized leachate samples. At 482 – 51,200 mg/L COD and 127 – 27,000 mg/L BOD5, the organic concentrations of the landfills were above the landfills’ discharge limits in Malaysia regardless of the landfill type. Ammonical-nitrogen was present in all the landfills and the highest value (880 mg/L) was obtained in the non-active sanitary landfill, whereas concentrations of heavy metals were highest (540 mg/L) in the active sanitary landfill leachate. The acute toxicity test revealed that LC50 as low as 1% v/v of the raw leachate was possible and showed that mortality and the corresponding Fish Leachate Toxicity index (FLLTI) decreased in the order of non-active sanitary (5.46), active sanitary (3.87), non-active non-sanitary (1.76) and the active non-sanitary (1.28) landfills, respectively. Bioaccumulation study revealed that about 3.2 μg/g and 2.1 μg/g of Zn and Fe, respectively were found in the fish after exposure to leachate pollution for 96 hours, as against 0.21 μg/g and 0.8 μg/g of the same heavy metals obtained in the control experiment (non-exposed fish), respectively. Similarly, tissue analysis of fish showed pale stains on the cellular compartments of the gills and liver. Microbial characterization of the leachate polluted soil indicated that regardless of the toxic effect on the environment, some bacteria species can survive namely Bacillus sp., Pseudomonas sp., Lysinibacillus sp., Rodococcus sp., Acinetobacter sp., Microbacterium sp., Brevundomonas sp., Stenotrophomonas sp., and Flavomonas sp. Bioaugmenting the polluted soil with different treatments (A,B,C) formed from the combination of the microbes showed that the highest heavy metal removal was achieved when Bacillus sp., Lysinibacillus sp. and Rodococcus sp. were combined as compared to other treatments (P < 0.05). Cu (86%), Zn (73%), Pb (70%), Fe (67%) and Mn (64%) were removed after 100 days of biomonitoring. The least heavy metal removal rate constant was observed for Cd (K = 0.0053 day-1). Therefore, the study concludes that raw landfill leachate in Malaysia is toxic to these fish species, yet the varied impact of leachate is a reflection of the variation in the heterogeneous nature of leachate across different landfills rather than differences in exposed fish species/types. Also, the use of isolated microbes from leachate contaminated soil to bioaugment the polluted soil is a potential approach for optimal removal of heavy metals from leachate polluted soil.